Acute effects of outdoor physical activity on affect and psychological well-being in depressed patients – A preliminary study. (March 2016) - Frühauf, Anika; Niedermeier, Martin; Elliott, Lewis R.; Ledochowski, Larissa; Marksteiner, Josef; Kopp, Martin
Abstract: Introduction: Physical activity (PA) is well established in the treatment of people with depressive symptoms. Most of this activity is done in an indoor setting. There is growing evidence that PA outdoors shows larger positive effects on affective states than PA indoors. The aim of the present study was to compare the affective experience of an acute outdoor exercise bout with indoor and sedentary equivalents for individuals with clinical depression. Method: 14 in-patients with mild to moderate depression were recruited during treatment in a mental health center. In a within-subjects experimental study, all participants completed three 60-min sessions: a sedentary control condition (SC), an indoor PA condition (IC), and an outdoor PA condition (OC). Mood, valence and activation were assessed throughout each session using the Mood Survey Scale (MSS), Feeling Scale and Felt Arousal Scale. Results: Concerning the MSS subscales, whilst patients in the SC exhibited minimal changes, significantly lower "excitement" scores and higher "activation" scores were reported following the OC. Affective activation also differed significantly between OC and IC. Conclusion: A single outdoor exercise bout showed greater affective improvements compared to indoor and sedentary equivalents for self-reported excitement and activation. As patients felt more active, an outdoor setting might be useful in overcoming listlessness during depression treatment. Due to methodological limitations associated with the pragmatic nature of the trial, findings must be interpreted with caution. Further trials should focus on wider feasibility and acceptability of outdoor exercise in depressive patients. Highlights: First study on affective changes after outdoor and indoor PA in depressive patients. Greater affective improvements after outdoor PA compared to a control condition. Depressive patients feel more activated after PA outdoors than indoors.